Experimental study on heat transfer characteristics of steam underwater direct-contact condensation - Chen Qian; Li Hui; Li Dongyang; Wen Jiming; Li Yong; Xiao Qi; Tan Sichao (Frontiers in Thermal Engineering, 2023)
Introduction: The direct-contact condensation (DCC) of steam under water injection is the basic thermodynamic process of the bubble deaerator. In order to understand the complex coupling behavior of strong turbulence and fast phase-change heat transfer involved in the process.Methods: This study uses a visualized method and convective heat transfer model.Results: Since the contact area is affected by steam injection flow and sub-cooled degree is affected simultaneously, the trend of the condensation heat-transfer coefficient depends on the degree of their respective effects under each condition, and the maximum variation of the coefficient exceeds 104 W/m2.°C. Moreover, they still effect the period of steam plume, and the maximum variation of the period was beyond 80 ms.Discussion: Calculated the average condensation heat transfer coefficient and then produces the variation law of heat transfer coefficient under various conditions in one steam plume evolution period.